Global trends and challenges in multimetric indices of biological condition. (March 2020) - Ruaro, Renata; Gubiani, Éder André; Hughes, Robert M.; Mormul, Roger Paulo
Graphical abstract: Highlights: Species indicating degradation are fundamental for environmental management. Choosing of criteria is a key element for developing tools of bioassessments. Multimetric indices are widely used, but are developed from varying approaches. MMIs comparisons increase by using common metrics, criteria and natural variability. Abstract: The use of multimetric indices (MMIs) of biological condition has been globally applied because they are practical tools that incorporate various biological metrics at different levels of ecological organization. However, the methods for developing and evaluating MMIs have been criticized. We reviewed the scientific literature to assess global processes for MMI creation and validation. We found a lack of common criteria for metric selection and determination of reference conditions, which hinders making comparable assessments across different programs and regions as well as for developing or refining future MMIs. We also present the ten metrics most commonly used in MMIs worldwide. Finally, we determined that differentiating natural variability from anthropogenic impacts is the major challenge in creating and applying MMIs. We offer our review to further the advancement and improvement of MMIs as standard bioassesment tools.